Research Progress of Circular RNA in Gastrointestinal Tumors - Fang, Na; Ding, Guo-Wen; Ding, Hao; Li, Juan; Liu, Chao; Lv, Lu; Shi, Yi-Jun (Frontiers in Oncology, 2021)
circular RNA (circRNA) is a closed ring structure formed by cyclic covalent bonds connecting the 5’-end and 3’-end of pre-mRNA. circRNA is widely distributed in eukaryotic cells. Recent studies have shown that circRNA is involved in the pathogenesis and development of multiple types of diseases, including tumors. circRNA is specifically expressed in tissues. And the stability of circRNA is higher than that of linear RNA, which can play biological roles through sponge adsorption of miRNA, interaction with RNA binding protein, regulation of gene transcription, the mRNA and protein translation brake, and translation of protein and peptides. These characteristics render circRNAs as biomarkers and therapeutic targets of tumors. Gastrointestinal tumors are common malignancies worldwide, which seriously threaten human health. In this review, we summarize the generation and biological characteristics of circRNA, molecular regulation mechanism and related effects of circRNA in gastrointestinal tumors.